PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN DESA (STUDI PADA DESA DI KABUPATEN ACEH SELATAN) - Arighi, Agung Muhammad; Darwanis, Darwanis (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research aims to test the influence of human resources Capacity, utilization of information technology as well as internal control against the timeliness of financial reporting village. The population in this research is the entire village in Aceh Selatan Regency. Sampling techniques in the study is simple random sampling. The research of using primary data obtained through the filling of the questionnaire. The data collected as many as 73 a detailed questionnaire from the 260 villages that existed in South Aceh Regency. Data processing using SPSS tool Version 22. Statistical analysis is used in logistic regression is. The results showed that collectively the variable capacity of human resources, utilization of information technology as well as internal control against the timeliness of financial reporting village. Each partially independent variable affect the timeliness of financial reporting Village.